A Wolbachia factor for male killing in lepidopteran insects - Susumu Katsuma; Kanako Hirota; Noriko Matsuda-Imai; Takahiro Fukui; Tomohiro Muro; Kohei Nishino; Hidetaka Kosako; Keisuke Shoji; Hideki Takanashi; Takeshi Fujii; Shin-ichi Arimura; Takashi Kiuchi (Nature Communications, 2022)
Bacterial symbionts, such as Wolbachia species, can manipulate the sexual development and reproduction of their insect hosts. Here, the authors identify a Wolbachia protein that interacts with a host masculinization factor and leads to male killing in lepidopteran insects.